Gambaran Tingkat Pengetahuan Dan Sikap Pasien Tentang Penatalaksanaan Non Farmakologi Konjungtivitis - Hartati Hartati; Sumarni Sumarni; Supriyo Supriyo (Prodi Keperawatan Purwokerto, 2021)
Background : Conjunctivitis is a common disease that can be experienced by everyone regardless of their race, gender, and social strata. Conjunctivitis can be contagious easily, so that in addition to pharmacological treatment non pharmacological treatment is also required. Every year, in Indonesia, conjunctivitis increases significantly, where in 2015 there were 1,528 cases, in 2016 1,769 cases. In order to prevent increase the self. Prevention management, people with conjunctivitis need have significant knowledge and skill. The purpose of this research is to know the description of the level of knowledge and attitude of patients about treatment of non pharmacological conjunctivitis.Methods : This research is quantitative with a descriptive method. Data from april 2016 until January 2017 using the questionnaire. population of 128 people with samples of the 97 people who are taken as a proportionate random sampling.The Results : Showed the average age of respondents has aged 26-35 (49,2%), has a junior high school education 48 respondens (49.5%), and 37 respondents (38,1%) worked as a laborer. More than half (51.5%) of the respondents have a low level of knowledge about the management of non pharmacological conjunctivitis and most of the 75 respondens (77.3%) have a negative attitude about therapy for non pharmacological conjunctivitis.Conclusion : It is expected that the hospital can provide health education to patients about non pharmacological conjunctivitis and leaflets related conjunctivitis treatment.